Parameters responsible for the degradation of CH3NH3PbI3-based solar cells on polymer substrates. (April 2016) - Dkhissi, Yasmina; Weerasinghe, Hasitha; Meyer, Steffen; Benesperi, Iacopo; Bach, Udo; Spiccia, Leone; Caruso, Rachel A.; Cheng, Yi-Bing
Abstract: Despite the rapid progress made in the field of perovskite solar cells, their instability remains a major obstacle for commercialization. Here, focus is placed on the stability of CH3 NH3 PbI3 solar cells on polymer substrates and the understanding of the factors influencing device degradation. A range of storage conditions is used, parameters such as light or temperature are isolated, and their impacts on the perovskite film examined. The severe loss in device performance is not predominantly correlated to the perovskite film deterioration, which implies that the device failure originates elsewhere. This study demonstrates that the hole transport material plays a significant role in the device degradation, and thus its optimization or removal can potentially lead to enhanced device lifetime. Graphical abstract: Highlights: A systematic study to investigate the sources of perovskite cell degradation. Perovskite devices fail without CH3 NH3 PbI3 films showing signs of degradation. Hole transport material affects device lifetime.